1998
DOI: 10.1303/jjaez.42.51
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Control of Diamondback Moth, Plutella xylostella, by Entomopathogenic Fungus, Beauveria bassiana. I. Laboratory Studies on Pathogenicity of Beauveria bassiana and Field Experiment.

Abstract: The pathogenicities of five isolates of Beauveria bassiana to Plutella xylostella were investigated. Treatment of 4th-instar larvae with each isolate resulted in 0%-100% mortalities at 5 days after inoculation. Detailed studies were made on the most virulent isolate, MG-Bb-1, obtained from P. xylostella, to determine its efficacy at different developmental stages of P. xylostella, doses, and humidities. MG-Bb-1 had high pathogenicity to lervae of all instars, but little pathogenicity to eggs, and almost no pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is important to develop alternative strategies such as entomopathogenic fungi to control P. xylostella populations, which will result in a reduction in the use of synthetic insecticides. Entomopathogenic fungal agents such as Beauveria bassiana (Balsamo) Vuellemin, Isaria (Paecilomyces) fumosoroseus (Wise) Brown and Smith and Metarhizium anisopliae (Metschnikoff) Sorokin have the potential to infect and kill P. xylostella . Among these fungal pathogens, the I. fumosorosea SCAU‐IFCF01 strain used in this study has demonstrated high effectiveness against P. xylostella , the first report of such rapid insecticidal activity against P. xylostella .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to develop alternative strategies such as entomopathogenic fungi to control P. xylostella populations, which will result in a reduction in the use of synthetic insecticides. Entomopathogenic fungal agents such as Beauveria bassiana (Balsamo) Vuellemin, Isaria (Paecilomyces) fumosoroseus (Wise) Brown and Smith and Metarhizium anisopliae (Metschnikoff) Sorokin have the potential to infect and kill P. xylostella . Among these fungal pathogens, the I. fumosorosea SCAU‐IFCF01 strain used in this study has demonstrated high effectiveness against P. xylostella , the first report of such rapid insecticidal activity against P. xylostella .…”
Section: Introductionmentioning
confidence: 99%
“…As the resistance of P. xylostella to chemical insecticides and B. thuringiensis toxins highlights a need for alternative tactics, an interest in incorporation of fungal biocontrol agents into its management systems has been increasing. To date, a few fungal agents including Beauveria bassiana (Balsamo) Vuellemin,10–13 Metarhizium anisopliae (Metschnikoff) Sorokin14 and Paecilomyces fumosoroseus (Wize) Brown and Smith15, 16 have been under investigation. Studies have demonstrated the potential for application of these fungal agents against the pest species and B. bassiana has proved the most promising 14…”
Section: Introductionmentioning
confidence: 99%
“…Conidia were produced on steamed rice, lyophilised to ca 5% water content at ambient temperature using a freeze dryer (model SimFD8‐6P; Sim International Group Co., Ltd, Beijing) and harvested from the grown medium through a vibrating sieve. The resultant powder, containing >1.2 × 10 conidia g −1 , was stored in 10 mL sealed plastic tubes in the dark at 4 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Isolates of different entomopathogenic fungal species, such as Zoophthora radicans (Brefeld) Batko, Beauveria bassiana (Balsamo) Vuellemin, Metarhizium anisopliae (Metschnikoff) Sorokin and Isaria ( Paecilomyces ) fumosoroseus (Wize) Brown and Smith, have the potential to infect and kill P. xylostella . Among these fungal pathogens, Isaria fumosorosea is one of the most promising fungal species for control of a great variety of arthropods, including P. xylostella , whiteflies and other insect pests …”
Section: Introductionmentioning
confidence: 99%